A estação do bronze final da Regueira - Almeida, Carlos A. Brochado de; Maia, Maria Isaura dos Santos; Moreira, Maria Manuel Lopes; Baptista, António José (História: revista da Faculdade de Letras da Universidade do Porto, 2019)
.